Low energy availability and low body fat of female gymnasts before an international competition - Silva, M.-R. G.; Paiva, T. (European Journal of Sport Science, 2015)
The purpose of the present study was to evaluate dietary intake and body composition of elite rhythmic gymnastics (RG) athletes prior to a competition event. Sixty-seven rhythmic gymnasts (18.7 ± 2.9 years old) of high performance level, with 36.6 ± 7.6 h of training/week were evaluated in order to collect training and competition data, medical and gynaecological history, detailed dietary intake and body composition before an international competition. The majority of the participants (n = 40; 59.7%) had already menstruated, but age of menarche was delayed (15.3 ± 1.3 years) and all revealed menstrual irregularities. Gymnasts' body mass (48.4 ± 4.9 kg) and body mass index (BMI; 17.4 ± 1.1 kg/m2) were below the normal for age, and height (1.66 ± 0.05 m) was normal or even slightly above normal for age. Body fat was 9.0 ± 2.0% with no significant differences between age strata. Gymnasts exhibited low energy availability (EA; 31.5 ± 11.9 kcal/kg fat-free mass (FFM)/day). The average carbohydrate and protein intakes were 5.1 ± 2.3 g/kg/day and 1.6 ± 04 g/kg/day, which correspond to 51.4 ± 7.2% and 16.9 ± 3.4% of total energy intakes, respectively; average fat contribution was 33.0 ± 5.3%. Low intakes of pantothenic acid, folate and vitamins D, E and K and of minerals, including calcium, iron and magnesium were reported. Intakes of thiamine, riboflavin, niacin, vitamins A, B-6, B-12, C and manganese and zinc were above-adequate (P < 0.05). Low EA, low body fat and micronutrient deficiencies are common among RG.